ASSESSMENT OF FACTORS INFLUENCING ADOPTION OF NARICT NEEM ORGANIC FERTILIZER AMONG SMALLHOLDER TOMATO FARMERS IN KADUNA STATE, NIGERIA - Iguda, Bashir Tanko; Yusuf , H. O.; Abubakar, Jamilu (FUDMA Journal of Sciences, 2024)
This study was designed to assess smallholder tomato farmer’s level of awareness of NARICT neem organic fertilizer as well as to determine the factors influencing its adoption by the smallholder tomato farmers in the study area. Four Local Government Areas (LGAs) were randomly selected from the four ADP zones of the state. One village was randomly selected from each of the four selected LGAs and then 11% of the tomato farmers from each of the four villages were randomly selected to arrive at the sample size of three hundred and fifty (350) tomato formers. Both inferential and descriptive statistics were used in the analysis of data. The mean age of respondents was found to be 42yrs for adopters and 35yrs for non-adopters, 96.9% were males for adopters and 22.1% are females for non-adopters respectively. The mean household size for the non-adopters was 11 persons and 8 persons for non-adopters. 94.3% of the interviewed farmers were aware of the NARICT neem organic fertilizer and 5.7% are not aware of the NARICT neem organic fertilizer. It was therefore concluded that even though about 54.3% of the respondents are aware of NARICT neem fertilizer, only about 45.7 % use it. Also, it was found out that the socio-economic and Institutional characteristics of the farmers have significant influence on the adoption of NARICT neem organic fertilizer. The result shows that socio economic factors such as farming experience, educational level, farm size, age and source of credit significantly influence adoption of the fertilizer...
Keywords: Factors influencing; Adoption of NARICT neem organic fertilizer; Smallholder tomato farmers